Description of immature stages of Hybosa acutangula Spaeth, 1913 (Coleoptera, Chrysomelidae, Cassidinae) - Świętojańska, Jolanta; Linzmeier, Adelita M. (Zootaxa, 2024)
The immature stages of Hybosa acutangula Spaeth, 1913, member of the tribe Cassidini Gyllenhal, 1813, are described in detail and compared with other members of Cassidini and Ischyrosonychini Chapuis, 1875 species. The eggs, oothecae and first instar larvae are described for the first time. The morphology of the immatures of H. acutangula, unusual for the species of the Cassidini tribe, was the impulse that initiated the research. The result of the comparative analysis is the conclusion that the morphological features of the immature stages of H. acutangula are a mixture of characters observed in representatives of the Cassidini and Ischyrosonychini tribes. The similarity to Ischyrosonychini may only be convergence, but it cannot be ruled out that there is a separate phylogenetic lineage within Cassidini, represented by H. acutangula. Verification of this hypothesis requires further research.